Kajian Tentang Perlakuan Jarak Antar Elektroda Tembaga Terhadap Kinerja Sensor Konduktivitas Listrik Tanah Tipe Kapasitif - Gede Andri; I Made Anom S. Wijaya; I Putu Gede Budisanjaya (Jurnal BETA (Biosistem dan Teknik Pertanian), 2015)
The measurement of EC can be conducted in two ways, namely electromagnetic induction and direct contact. This study using capacitive direct contact. The aims of this study were to determine the relationship between distance, shape and electrode materials to the measurements performance, and to determine to treatment that has the best performance. The study was started by designing the electrodes then continued by functional test and performance test. The treatments used was electrodes distances of 3, 6, 9, 12 & 15 mm. The electrode probe was inserting into the soil with the depth of 20 cm to get the frequency and at the same time soil sample was collected for analyzed in the laboratory to get the EC values. Based on those data the relationship of between soil frequency and EC were then analyzed. The results indicated that the best performance electrode with distance 3 mm. The equation of soil frequency and EC was EC = 0.186875 Fsoil - 10.5695 with R2 = 0.861, RMSE = 0.04, stability = 0.04 and respond time = 37.35 second.